2008
DOI: 10.1029/2007ja013012
|View full text |Cite
|
Sign up to set email alerts
|

The midlatitude F2 layer during solar eclipses: Observations and modeling

Abstract: [1] We conducted a statistical analysis on the changes in foF2 during seven eclipse events on the basis of the data derived from 23 ionosonde stations. To model eclipse effects on the ionosphere, we constructed a solar spectrum model for solar eclipses. The background hmF2, local time, solar cycle, and dip angle effects on the ionospheric response to solar eclipses are investigated in the four controlled case studies. Both the measurements and simulations show that the eclipse effect is larger in the midday th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 47 publications
8
68
1
Order By: Relevance
“…Figure 9a shows that the delay time of the ionization decrease increases with height from foE to foF2 in agreement with earlier observations (e.g., Jakowski et al 2008) and simulation results (e.g. Le et al 2008).…”
Section: Vertical Sounding Datasupporting
confidence: 81%
See 2 more Smart Citations
“…Figure 9a shows that the delay time of the ionization decrease increases with height from foE to foF2 in agreement with earlier observations (e.g., Jakowski et al 2008) and simulation results (e.g. Le et al 2008).…”
Section: Vertical Sounding Datasupporting
confidence: 81%
“…As a result, it is reasonable to assume that the E layer was further depleted at around the time of the maximum obscuration at the Dourbes station. Based on simulation studies, Le et al (2008) discussed the eclipse effects on electron density and corresponding delay time considering control factors such as the background hmF2, local time and solar zenith angle, solar cycle, and dip angle. According to their study, an eclipse will produce a relatively smaller change in NmF2 associated with a higher time delay if the hmF2 is higher.…”
Section: Vertical Sounding Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The F2 region behavior may be quite different accompanied with various amplitudes of decrease or even a small increase in the electron concentration. Combining the measurements and four controlled case simulations, Le et al (2008b) found that most of the observed differences in the behavior of the peak electron density of the F2 layer (NmF2) during eclipses can be attributed to the differences in O + loss rates brought about by the background differences in the neutral molecular densities. Despite many studies on the eclipse effects of the ionosphere over the eclipse region, there are still rarely studies on the ionospheric disturbances in the magnetically conjugate regions.…”
Section: Introductionmentioning
confidence: 99%
“…Study of the ionospheric response to a solar eclipse has been in place for decades, and extensive studies have been made with various experimental techniques, such as ionosondes, incoherent scatter radar, rockets, Faraday rotation measurements, global positioning system and satellite measurements (Evans, 1965a, b;Klobuchar and Whitney, 1965;Rishbeth, 1968;Hunter et al, 1974;Oliver and Bowhill, 1974;Cohen, 1984;Salah et al, 1986;Cheng et al, 1992;Farges et al, 2001;Tomas et al, 2007) as well as theoretical modeling (Le at al., 2008a, and references therein). Both the measurements and simulations show that the eclipse effect is larger in the midday than in the morning and afternoon, and also the decrease in electron concentration is greater in the F1 region than in the E region (Le at al., 2008a). The eclipse effect in the F2 region is larger at high solar activity than at low solar activity.…”
Section: Introductionmentioning
confidence: 99%